IMPLEMENTASI KEBIJAKAN SISTEM JAMINAN KESEHATAN IBU HAMILDALAM RANGKA MEMPERCEPAT PENCAPAIANMILLENIUM DEVELOPMENT GOALS- MDG′S DI KOTA BANJARMASIN, KALIMANTAN SELATAN - Suroyo, Anis (JPAP: Jurnal Penelitian Administrasi Publik, 2016)
Maternal and child health is one of the Millennium Development Goals MDG's 2015 global agreement targeting the maternal mortality rate in Indonesia can be reduced to 102 per 100,000 live births in 2015. Efforts to suppress AKI continue to be pursued, including the provision of health services for pregnant women. In 2014, the government began implementing a National Health Insurance (JKN) nationally. Implementation of the JKN program causes Delivery Guarantee (Jampersal) for pregnant women deleted. The deletion encourage local governments to be creative pressing AKI with JKN program and the Regional Health Insurance (Jamkesda). Policy of Implementation Security System Maternal Health in Banjarmasin, which inhibits MCH program because the program JKN knows no territorial, pregnant women can choose the health care she likes, while the MCH program is monitoring the health of pregnant women by the cantonal ie PWS-KIA for evaluation and program planning region. The cause of the mortality rate among pregnant women in the city of Banjarmasin is due late in delivery to the referral occurs as a result of factors helper (service providers at a basic level), delayed detection of high risk so that the condition of pregnant women who were referred is severe enough, and too late to reach health care at the level of referral services. Lack of adequate resources, facilities and infrastructure that do not support and quality of service at referral level is a factor causing delay in rescue efforts maternal health. JKN program bureaucratic system does not support MCH programs, thus largely independent midwives are reluctant to deal with pregnant women / mothers give birth this was due to a convoluted bureaucracy and services / approved rates are too low in accordance with Law of the Ministry of health No 59, 2014. Keywords: implementation of policies, health insurancepregnant women.